2022
DOI: 10.1101/2022.04.26.489557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortical response variability is driven by local excitability changes with somatotopic organization

Abstract: Identical sensory stimuli can lead to different neural responses depending on the instantaneous brain state. Specifically, neural excitability in sensory areas may shape the brain’s response already from earliest cortical processing onwards. However, whether these dynamics affect sensory domains globally or occur on a spatially local level is largely unknown. We studied this in the somatosensory domain of 38 human participants with EEG, presenting stimuli to the median and tibial nerves alternatingly, and test… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 92 publications
(167 reference statements)
1
0
0
Order By: Relevance
“…The phase reversal phenomenon could be attributed to the differential activation of neural populations within the somatosensory cortex, as found by several studies 26 , 30 , 39 , 40 . Compared to ECoG SSEP studies, the traces acquired from EEG show reduced amplitude but similar latencies, as found in similar studies 41 . Channels 209, 210, 212, and 215, expected to be located posterior to the central sulcus, exhibit the desired SSEP waveform with a negative peak (N) followed by a positive (P).…”
Section: Discussionsupporting
confidence: 79%
“…The phase reversal phenomenon could be attributed to the differential activation of neural populations within the somatosensory cortex, as found by several studies 26 , 30 , 39 , 40 . Compared to ECoG SSEP studies, the traces acquired from EEG show reduced amplitude but similar latencies, as found in similar studies 41 . Channels 209, 210, 212, and 215, expected to be located posterior to the central sulcus, exhibit the desired SSEP waveform with a negative peak (N) followed by a positive (P).…”
Section: Discussionsupporting
confidence: 79%